Testing Minsky’s Financial Fragility Hypothesis for Turkey’s Public Finances - Can, Cansin Kemal; Canöz, Ismail (Public Finance Quarterly, 2020)
This paper gauges the degree of fiscal vulnerability in Turkey from a Minskian perspective. Succinctly speaking, Minsky’s financial stability hypothesis states that the government should apply hedge financing at least sporadically and pursue countercyclical fiscal policies to restore stability. We calculated two fiscal fragility indices based on Minsky’s hypothesis to examine the recent trends in Turkish public finances. According to our findings, Turkish fiscal balances are in a deteriorating trend and heading towards (ultra)Ponzi financing which is evidenced by the plummeting values of the fiscal fragility index. The results are suggestive that currently the fiscal performance in Turkey is waning gradually and current fiscal posture is not on a par with past years. Worsening fiscal balances emit a signal for a looming fiscal crisis and it is evident that this trend should promptly be reversed by the aid of appropriate expedients. Quitting the use of procyclical fiscal policies, building up public confidence by primary balance generation, implementing full-fledged tax reform, restructuring contingent liabilities, proper scrutiny of expenditures, reducing profligacy are among the policy options available for the government. Notwithstanding the abundance of alternative fiscal policies, the current Covid-19 pandemic is quite a hindrance to attaining intended outcomes regarding fiscal stability.